INISIASI STRATEGI MANAJEMEN LEMBAGA PENDIDIKAN ISLAM DALAM MENINGKATKAN MUTU SUMBER DAYA MANUSIA ISLAMI DI INDONESIA DALAM MENGHADAPI ERA GLOBALISASI - M Ihsan Dacholfany (Universitas Muhammadiyah Metro, 2017)
Islamic educational institutions are expected to produce human resources who is faithful and devoted to have insight into the science and technology. To achieve these expectations,of course Islamic educational institutions should revitalize the role of educational institutions to be able to play an optimal role in realizingacademic excellence for education, for industrial relevance, for contribution for new knowledge, and for empowerment.Recognizing the importance of the process of improving the quality of human resources, government, managers of educational institutions, educators and learners strive to accomplish the purpose, vision and mission through a variety of activities to build better quality education through the development and improvement of curriculum and evaluation system, improvement of facilities education, development and procurement of teaching materials, and training for teachers and education personnel.Keywords: Initiation, strategy management, human resources